(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Dimethyl disulfide (DMDS), the natural biopesticide extracted from Allium spp., was evaluated against root-knot nematode (Meloidogyne incognita) of tomato (Lycopersicon esculentum L.) in greenhouse pot culture. All concentrations of DMDS viz. 30 ml, 60 ml, and 80 ml and Aldicarb @ 2g per square meter of soil were effective against root-knot disease under both wet and dry conditions of soil. Nematode incidence was reduced drastically by higher dose of DMDS and Aldicarb @ 2g but did not accelerate vegetative growth of tomato plant especially when tomato seedlings were transplanted immediately after soil treatment. Low concentration of DMDS (30 ml per square meter of soil) was found appropriate for controlling root-knot nematode of tomato, accelerating saprophytic nematode population in soil and also enhancing vegetative growth of tomato plant under dry condition of soil. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11759 Bangladesh J. Agril. Res. 36(4): 685-695, December 2011